Speechless - King, Robert; Harlin, Renny 1959-; Davis, Geena 1956-; Underwood, Ron 1953- (MGM/UA Home Video, 1994)
It was a match made in heaven...almost. Two witty, intelligent insomniacs, Kevin and Julia, meet over the last box of sleeping pills at an all-night convenience store and are immediately attracted. They share the evening of passion and romance and discover that they have a lot in common...maybe too much in common. When they learn that they're both speechwriters - but for opposing political campaigns - the sweethearts quickly move from speechless to ruthless, and drop the pillow talk for serious verbal jabbing. But the more they stab each other in the back and insult each other directly, the more they realizes that true love doesn't always follow along party lines.